CAADP (2026–2035): Conversation towards domestication within Ethiopia’s agri-food systems policies and investment plans - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
CAADP (2026–2035): Conversation towards Domestication within Ethiopia’s Agri-Food Systems Policies and Investment Plans was co-organized by the Ministry of Agriculture (MoA) and the International Food Policy Research Institute (IFPRI). The half-day meeting took place on October 27, 2025, at the ILRI Campus in Addis Ababa, Ethiopia.